Rola elementów interaktywnych w systemach zdalnej edukacji - Dębska, Barbara; Kubacka, Agnieszka (The role of interactive elements in distance learning, 2005)
In recent years, the potential of distance learning methods in education has been receiving an increasing amount of interest in the Polish higher education milieu. Numerous academic institutions choose to supplement their educational offer by introducing elements of distance learning. Some schools also develop self-contained on-line courses, whose participants can graduate with a course certificate or a higher education diploma. The project that has been carried out for the last two years in the State Higher School of Vocational Education in Krosno (PWSZ) is aimed at introducing elements of e-leaming into the teaching of the subject entitled “ Algorithms and data structures” The subject is taught to Is' year students. First, appropriate didactic materials were developed for a section entitled “RAM engine”. A programme simulating the work of the RAM engine was developed and put on the school server. This enabled the students to easily access and download the compiler and a set of examples that simulate the work of the engine. As a result, in the test following this section of material, the pass rate for the students rose from the average of 25% to 79%. These positive results have encouraged us to continue the work on the e-leaming portal. Other multimedial lessons were prepared to cover the areas of: computational complexity, dynamic structures, decision trees, heapes and priority queues, as well as sorting algorithms. The portal was then further extended by adding modules that ensure better network data security and assist the processes of course design and organization. The didactic materials are collected in two databases: a static and a dynamic one. The static database includes sets of definitions, exercises and tests. The dynamic one includes programmes containing animations, simulations or interactive elements. Much attention was paid especially to the use of interactive elements in multimedial lessons devoted to sorting algorithms. Various research have shown that the option of adapting training materials to the needs of a given student makes the learning process much more effective. For this reason, in the work on the portal much attention was put to the flexibility of the educational model. In the first stage of the work, a special flexible training programme was created. The programme has a module that controls the flow of data in a way that adjusts the training process according to the performance of the students. For example, depending on the answers provided by the students, several subsequent questions may be omitted. Similarly, if a student did not answer a particular question or needed help to answer it, the question may be posed again in the testing process. At present, the work on the project concentrates mainly on creating a system that would enable to generate tests that would incorporate questions of a predetermined level of difficulty. The research on the effectiveness of the adopted and the planned solutions will be continued and presented also at this conference.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 380-382